Light received by embryos promotes postnatal junior phenotypes in a seabird. (27th August 2022) - Ruiz-Raya, Francisco; Noguera, Jose C; Velando, Alberto
Abstract: Light is a salient and variable ecological factor that can impact developmental trajectories of vertebrate embryos, yet whether prenatal light environment can act as an anticipatory cue preparing organisms to cope with postnatal conditions is still unclear. In asynchronous birds, last-laid eggs are particularly exposed to sunlight as parental incubation behavior becomes intermittent after the hatching of senior chicks. Here, we explore whether natural variations in prenatal light exposure shape the distinctive phenotype showed by last-hatched chicks of a semi-precocial seabird, the yellow-legged gull ( Larus michahellis ), potentially preparing them to cope with the postnatal competitive context. To do this, we manipulated the amount of light received by last-laid eggs (within a natural range) during last stages of embryonic development. Prenatal exposure to light cues promoted the development of the resilient "junior phenotype" exhibited by last-hatched gull chicks, characterized by accelerated hatching, increased begging behavior and a slower growth rate. These developmental and behavioral adjustments were accompanied by down-regulation of genes involved in metabolism and development regulation (SOD2 and TRalpha), as well as changes in the HPA-axis functioning (lower baseline corticosterone and robust adrenocortical response). Junior chicks exposed to light cues during the embryonic development showed longer telomeres during the early postnatal period, suggesting that light-induced adjustments could allow them to buffer the competitive disadvantages associated with hatching asynchrony. Our study provides evidence that postnatal junior phenotypes are, at least in part, prenatally shaped by light cues that act during a critical temporal window of developmental sensitivity. Abstract : Avian embryos may be exposed to variable light environments as parental incubation behavior becomes intermittent after hatching of senior chicks. We found that natural variations in the prenatal light environment shape the phenotype exhibited by last-hatched gull chicks, characterized by accelerated hatching, increased begging behavior, and slower growth rates. These adjustments were accompanied by changes in gene expression, endocrine profiles and telomere dynamics, and could allow junior chicks to buffer competitive disadvantages associated with hatching asynchrony.